Hydrogen Production by Hybrid photovoltaic Thermal System - Amori, Karima E.; Salman, Sameer M.; Kareem, Zahraa Hashim (Al-Nahrain Journal for Engineering Sciences, 2017)
Hydrogen fuel is a good alternative to fossil fuels. It can be produced using a clean energy without contaminated emissions. This work is concerned with experimental study on hydrogen production via solar energy. Hybrid photovoltaic thermal system (PV/T) is used to convert solar radiation to electrical and thermal energy. The electrical energy is used to analyze water into hydrogen and oxygen by using alkaline water electrolyzer with stainless steel electrodes. The absorbed thermal energy is used to heat circulating water inside the copper serpentine pipe fixed on the back surface of the PV panel. A perforated pipe connected on the upper edge of PV panel is used to spray a thin layer of water on the PV panel surface for auxiliary cooling and improve the generated electrical power. The hydrogen production system is tested at different temperature of electrolysis water (40, 45, 50, 55, 60)?C. The experimental results show that the PV module electrical efficiency is improved by (14.31)%. while the power generated was enhanced by (3.94 to 15.40)%. The maximum hydrogen production rate is 153.3 ml/min, the efficiency of the system is 20.88% and the total amount of hydrogen produced in one day is 220.752 liter.